KEARIFAN LOKAL DALAM TRADISI PANEN MADU HUTAN DI DAERAH AMFOANG, KABUPATEN KUPANG - Junetry Olivia Haenael; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the local wisdom of the Amfoang community in East Nusa Tenggara through the forest honey harvesting tradition. This tradition not only has economic value but also contains cultural, social, and spiritual significance. This study used a literature review method with a qualitative descriptive approach, utilizing various written sources of relevant research. The findings indicate that the Amfoang community's forest honey harvesting tradition embodies local wisdom values, such as cooperation, responsibility, and gratitude for natural gifts. The harvesting process is led by traditional leaders with a system of dividing tasks and harvests based on customary rules. Before the activity begins, the community holds a ritual as a form of respect for ancestors and a request for safety. Furthermore, this tradition demonstrates a harmonious blend of customs and Christian-Protestant teachings through prayers and hymns that accompany the activity. Thus, the Amfoang honey harvesting tradition symbolizes the preservation of a sustainable local culture full of life values.